Candida albicans β-Glucan Exposure Is Controlled by the Fungal CEK1-Mediated Mitogen-Activated Protein Kinase Pathway That Modulates Immune Responses Triggered through Dectin-1 - Galán-Díez, Marta (American Society for Microbiology (ASM), 2010)
Innate immunity to Candida albicans depends upon the recognition of molecular patterns on the fungal cell wall. However, the masking of major components such as β-glucan seems to be a mechanism that fungi have evolved to avoid immune cell recognition through the dectin-1 receptor. Although the role of C. albicans mitogen-activated protein kinase (MAPK) pathways as virulence determinants has been established previously with animal models, the mechanism involved in this behavior is largely unknown. In this study we demonstrate that a disruption of the C. albicans extracellular signal-regulated kinase (ERK)-like 1 (CEK1)-mediated MAPK pathway causes enhanced cell wall β-glucan exposure, triggering immune responses more efficiently than the wild type, as measured by dectin-1-mediated specific binding and human dendritic cell (hDC)- and macrophage-mediated phagocytosis, killing, and activation of intracellular signaling pathways. At the molecular level, the disruption of CEK1 resulted in altered spleen tyrosine kinase (Syk), Raf-1, and ERK1/2 activations together with IκB degradation on hDCs and increased dectin-1-dependent activator protein 1 (AP-1) activation on transfected cells. In addition, concurring with these altered pathways, we detected increased reactive oxygen species production and cytokine secretion. In conclusion, the CEK1-mediated MAPK pathway is involved in β-glucan exposure in a fungal pathogen, hence influencing dectin-1-dependent immune cell recognition, thus establishing this fungal intracellular signaling route as a promising novel therapeutic target.